P0677CONTRAST-ENHANCED ULTRASOUND TO ASSESS RENAL MICROCIRCULATION IN PATIENTS WITH CHRONIC KIDNEY DISEASE. (6th June 2020) - Garessus, Jonas; Brito, Wendy; Loncle, Nicolas; Vannelli, Anna; Wuerzner, Grégoire; Schneider, Antoine; Pruijm, Menno
Abstract: Background and Aims: Vascular factors such as capillary rarefaction, increased vascular stiffness and reduced vasodilatation due to endothelial dysfunction probably play an important role in the pathophysiology of chronic kidney disease (CKD). However, our understanding of the underlying mechanisms is hampered by the lack of non-invasive techniques to quantify renal microvasculature in humans. The aim of this study was to assess whether contrast-enhanced ultrasonography (CEUS) can identify (1) differences in renal microcirculation and (2) the degree of nitroglycerin-induced vasodilatation (NIV) as a measure of renal flow reserve between CKD-patients and age-matched healthy volunteers. Method: All participants underwent CEUS under standardized conditions. Sonovue© (0.015 ml/kg/min) was perfused as contrast agent until a steady state was obtained, followed by four destruction-refilling sequences. Outcome measure of CEUS was the mean (change in) perfusion index (PI) of the outer renal cortex (see figure for an example ). In a subgroup of participants, CEUS was repeated before and five minutes after the sublingual administration of nitroglycerin (0.2mg). Renal resistive index (RRI) as a measure of vascular stiffness was also measured at each time point with Doppler ultrasound. Results: A total of 38 healthy volunteers (aged 50±8 years, eGFR 95±13 ml/min/1.73 m, 69% women) and 18 CKD stage 2-3 patients (aged 55±15 years, eGFR 64±32 ml/min/1.73m, 56% women) were included. Renal PI was significantly lower in CKD patients (1304±762 vs 2989 ±2503 arbitrary units, p=0.034), whereas RRI did not differ (0.66± 0.07 vs 0.63± 0.04), p=0.10). PI was lower in CKD due to vascular nephropathy (n=3) or interstitial nephritis (n=4) than CKD due to diabetes (n=4) or other causes (7). In continuous analysis, PI correlated with eGFR (spearman's r=0.54, p=0.005) but not with blood pressure. Renal PI did not change after nitroglycerin in both groups; RRI decreased in healthy (from 0.64±0.03 to 0.61±0.02, p=0.01) but not in CKD patients. Conclusion: In this study, contrast-enhanced ultrasound identified important alterations in renal microperfusion in patients with moderate CKD. Whether a low perfusion index predicts renal function decline needs further study. Sublingual nitroglycerin seems to have limited potential as a new test of renal flow reserve.